PENGARUH KEGIATAN EKONOMI INTERNASIONAL TERHADAP PENINGKATAN CADANGAN DEVISA DI INDONESIA - Nisa Ussa'diyah (2023)
Foreign exchange reserves for a country are considered important and inseparable from international economic activities. Foreign exchange becomes a vital indicator to prove a fundamental strength in a country's economy. The increase in foreign exchange reserves was influenced by several factors in international economic activities, such as foreign direct investment, external debt and export activities. The purpose of this study is to determine the effect of foreign direct investment, foreign debt and exports on increasing Indonesia's foreign exchange reserves. This research data is from 1990-2021. The Error Corection Model (ECM) was chosen as the method in this study. The results of the model analysis that foreign direct investment has a significant effect on increasing foreign exchange reserves in the long term but in the short term doesn't have a significant effect because incoming foreign investment needs to be reprocessed, such as to increase domestic production so that it can increase international trade activities which will later increase foreign exchange reserves. Foreign debt in both the long and short term has a significant effect on the increase in foreign exchange reserves, where foreign debt that enters directly accumulates into the state budget as well as the country's total foreign exchange reserves. Exports in the long term have a significant effect on increasing foreign exchange reserves but in the short term don't have a significant effect because the results obtained from export activities are also used in import financing so that the influence of exports cannot be seen in the short term.